An Immune-CNS Axis Activates Remote Hippocampal Stem Cells Following Spinal Transection Injury - Dehler, Sascha; Lou, Wilson Pak-Kin; Gao, Liang; Skabkin, Maxim; Dällenbach, Sabrina; Neumann, Andreas; Martin-Villalba, Ana (Frontiers in Molecular Neuroscience, 2018)
External stimuli such as injury, learning, or stress influence the production of neurons by neural stem cells (NSCs) in the adult mammalian brain. These external stimuli directly impact stem cell activity by influencing areas directly connected or in close proximity to the neurogenic niches of the adult brain. However, very little is known on how distant injuries affect NSC activation state. In this study we demonstrate that a thoracic spinal transection injury activates the distally located hippocampal-NSCs. This activation leads to a transient increase production of neurons that functionally integrate to improve animal’s performance in hippocampal-related memory tasks. We further show that interferon-CD95 signaling is required to promote injury-mediated activation of remote NSCs. Thus, we identify an immune-CNS axis responsible for injury-mediated activation of remotely located NSCs.